Priority‐based target coverage in directional sensor networks. Issue 6 (1st November 2018) - Zarei, Zahra; Bag‐Mohammadi, Mozafar
Abstract : The target coverage optimisation is an important problem in directional sensor networks (DSNs). In this study, the authors present a novel algorithm, called cover critical target first (CCTF), for improving the coverage ratio in DSN. CCTF simultaneously maximises the number of covered targets, reduces the number of active sensors, and extends network lifetime. For a set of uncovered targets, CCTF always finds the highest priority target which has the minimum number of covering sensors. Among sensors that could cover this target, CCTF activates a sensor that covers more additional targets besides the found target. CCTF's performance is evaluated in terms of coverage ratio, the number of active sensors, and power consumption through extensive simulation. The simulation indicates that CCTF is robust against orientation and localisation errors.